Participatory research in Ikulwe-Iganga District, Uganda - Kayuki, KC; Wortmann, Charles S. (International Center for Tropical Agriculture, 1999)
A participatory approach to research on system improvement was initiated in five communities around Ikulwe District Farm Institute in Iganga District, Uganda. The site is located in the southeastern tall grassland zone, where perennial and annual crops are produced in mixed farming systems. Farmers identified and prioritized 15 problems related to crop production using a PRA approach. Crop pests and diseases predominated; soil-related problems included low soil fertility and soil erosion. Other problems included low crop yields and unreliable rainfall. However, the priorities change as new problems are identified during regular semi-annual planning and evaluation meetings. Farmers and researchers agreed to focus research on Africa cassava mosaic virus, groundnut rosette virus, bean diseases, banana weevil, soil erosion control and soil fertility management. Several crop varieties have been evaluated for either tolerance or resistance and farmers have adopted Nanse 2 and SS4 cassava varieties; K131, K132, MCM 2001, MCM 3030, OBA 1, UBR (92) 32 bean varieties; some sweet potato varieties; and two upland rice varieties. Farmers are paring corms to control banana weevils, and researchers have promised a cheaper alternative to the hot water treatment with which farmers had experimented. Canavalia, Mucuna, Crotolaria, and lablab were evaluated as either green manure or improved fallow for soil fertility improvement, and for their incorporation into the farming systems. Information obtained from FPR and on-station research was used to develop a decision guide to the use of these species in Eastern and Central Uganda. Living barriers of vetiver grass were evaluated and are now being used for controlling soil erosion. Through independent experimentation farmers have found Tephrosia effective in controlling root rats (Tachyoryctes splendens).